Prevalence of hypertension among adolescents - Dr Pranam GM; Dr Usha Pranam; Dr Manjunath G A (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Adolescence is a signiﬁcant period of growth and maturation. The emergence of obesity and its sequel as public health problems has renewed interest in the adolescents as Overweight and obesity act as risk factors for obesity related diseases. Familial aggregation of blood pressure is noted among adults, which has been traced to childhood, as early as one year of age. Methods: a cross sectional study involving 1000 boys and girls each were subjected to measurement of anthropometry, blood pressure and BMI. Results: The Incidence of Raised Blood Pressure in our study was 1.3%. The mean systolic blood pressure in boys increased from 102.75±3.24mmHg at 12years of age to 105.85±3.58 mmHg at 16years. In girls it rises from 102.04±2.53mmHg at 12 years to 106.48±3.59 mmHg at 16 years. The mean diastolic blood pressure increased from 66.85±3.45 mmHg at 12years of age to 67.95±4.24 mmHg at 16years, in boys. In girls it rises from 66.90±3.38mmHg at 12years to 68.95±4.53 mmHg at 16years. Blood pressure recordings showed an increasing trend steadily with age in the present study. Conclusion: There is a strong correlation between systolic blood pressure and weight and height in both sexes. Majority of the children who were labeled as hypertensive’s are likely to be suffering from essential hypertension, because of the asymptomatic nature of their condition. Hence the adolescent period the most precious stage for early detection and primary prevention on hypertension.